Application of Wound Dressings from Chitosan-Alginate-Collagen Biocomposites - Rachmawati, Yuliana Dwi; Purwaningtyas, Fiska. Y. (PT FORMOSA CENDEKIA GLOBAL, 2024)
Wound dressings are materials used to speed up the wound healing process and can make the healing condition better. The aim of this research is to form a biocomposite that originates from chitosan, alginate and collagen as well as looking at appropriate compositional comparisons to provide ideal biocomposite results. This research was carried out at the Chemical Engineering Laboratory, Muhammadiyah University of Gresik. The method used is a drying process at room temperature on a thin glass printer for 24 hours. The results of research on FTIR analysis of this biocomposite membrane contain alkyl amine groups, alkane compounds (C-H), NO2 bonds, aldehyde compounds, ketones, carboxylic acids, esters or bonds (C=O), alkane compounds (C-H), phenol compounds, alcohol monomers. , hydrogen bond alcohol (O-H). Analysis of the swelling test values ​​obtained were, 146%, 236%, 243%, 317%, and 474%.